Pfizer COVID19 vaccine is not associated with acute cardiovascular events excluding myocarditis- a national self-controlled case series study - Lital Keinan Boker; Ronen Fluss; Rita Dichtiar; Alina Rosenberg; Maya Ben-Lassan; Amit Huppert (BMC, 2024)
Abstract Background Despite publications assuring no increased risk for acute cardiovascular events (excluding myocarditis) and sudden death following administration of COVID19 vaccines, these issues still stir much public ado. We assessed the risk for acute cardiovascular events that require hospitalization (excluding myocarditis) and for mortality in the short-term following administration of the second dose of the Pfizer COVID19 vaccine in Israel. Methods Using a self-controlled case series (SCCS) study design and national databases, all second-dose vaccinees, who had not been diagnosed with COVID19 and who had an acute cardiovascular event (acute myocardial infarction/acute stroke/acute thromboembolic event) that required hospitalization in the 60 days following vaccine administration between Jan 11th, 2021 and Oct 31st 2021, were included. A similar analysis was carried out for mortality. The first 30 days following vaccination were defined as risk period while the next 30 days were defined as control period. The probability for an event between these periods was compared using a conditional logistic regression model, accounting for sex, age group, background morbidity and seasonal risk. Results Out of 5,700,112  second dose vaccinees, 4,163 had an acute cardiovascular event in the 60 days following vaccine administration. Following exclusion of 106 due to technical considerations, 1,979 events occurred during the risk period and 2,078 during the control period: Odds ratio, OR = 0.95, 95% confidence interval, CI 0.90-1.01, p = 0.12. Adjusted OR was similar (OR = 0.88, 95%CI 0.72-1.08). Stratifying by age showed no increased risk in any age group. Mortality assessment indicated low number of events in both periods. These results were consistent in sensitivity analyses. Conclusions There was no increased risk for acute cardiovascular events (excluding myocarditis) in the risk period compared to the control period following administration of the second dose of Pfizer COVID19 vaccine. Mortality data raised no concerns either, but may have been biased.